MANAGEMENT OF SELF-CONCEPT, DISRUPTIVE BEHAVIOR AND AGGRESSION THROUGH ART AND BEHAVIOR THERAPY AMONG INTERNALLY DISPLACED CHILDREN - Gul, Ruqaia; Irshad, Erum; Amjad, Rabia (Journal of Ayub Medical College Abbottabad, 2021)
Background: This study was conducted to explore the occurrence of aggression, disruptive behavior and nature of self-concept among internally displaced and un-displaced children. This study also examines the effectiveness of art therapy and progressive muscle relaxation (PMR) technique of behavior therapy in the treatment of psychological problems among internally displaced children. Methods: In this cross-sectional study a semi-structured interview and Beck Youth Inventory for children and adolescents (2nd edition) were used for assessment. The sample comprised 192 internally displaced and 90 un-displaced children. After taking formal permission from head of the schools, internally displaced children were assessed in their schools arranged for them at Jalozi camp, whereas un-displaced children were assessed at different schools of settled areas in Peshawar. Independent sample t-test was used to analyze mean differences, standard deviation and t-values. Results: Results supported the hypothesis. Internally displaced children showed higher levels of aggression (39.38±6.60) with t (280) = 8.57, and disruptive behavior (40.97±3.90) with t (280) = 6.76, and lower levels of self-concept (48.71±8.31) with t (280) = -15.32. Conclusion: Internally displaced children showed high levels of aggression and disruptive behavior, whereas their self-esteem was lower than the un-displaced children. This study also provides support to the idea that art therapy and technique of behavior therapy can be helpful in treatment of post trauma psychological issues in children. Keywords: Aggression; Disruptive behavior; Self-concept; Internally displaced and un-displaced; Children; Art therapy; Behavior therapy; Progressive muscle relaxation technique